Comparison of Different Criteria and Analytical Models for the Analysis of Composite Cylinders Assisted by Online Software - Eduardo A. W. de Menezes; Clara S. Theisen; Thiago V. P. Farias; Gabriel M. Dick; Maikson L. P. Tonatto; Sandro C. Amico (Applied Mechanics)
Due to their higher strength-to-weight ratio and ability to operate in harsh environments, the usage of fiber-reinforced cylindrical shells experienced a significant increase in the past decades. The key novelty of this study lies in implementing dual analytical approaches to address the complex failure mechanisms and stress distributions in composites. Two distinct theoretical solutions were investigated, membrane theory and Mindlin–Reissner theory, for failure prediction in filament-wound structures, while uniquely providing a platform for easy comparison of theoretical approaches. Experimental data from different setups, materials, and winding angles were collected in the literature and compared using the developed online MECH-Gcomp software. Failure analysis was also carried out by applying five different failure criteria well-established for composite materials. The results from the Mindlin–Reissner theory showed 46.9% deviation and those for the membrane theory 36.2% deviation, considering more than 120 cases. Sobol sensitivity analysis identified pressure (P), transverse tensile strength, winding angle, and radius as the most influential parameters regarding the index of failure of composite cylinders.